Analisis Dinding Penahan Tanah Tebing Sei Seruyan Desa Pembuang Hulu Kecamatan Hanau: Analysis Of Sei Seruyan Cliff Soil Retaining Walls, Pembuang Hulu Village, Hanau District - Indriani, Lilis (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
River buffers are an important part of a road network system because they have a significant effect if the river collapses or if it does not function properly. Because riverbanks are structures that cross roads and other traffic, the collapse of riverbanks will reduce or withstand traffic and also cause buildings that stand alongside eroded rivers and landslides, which in turn will disrupt the comfort of community traffic and live and disturb economic relations. So it is very important to calculate the structure of the cliff building in Pembuang Hulu Village, Hanau District, so that it does not endanger the road users and community comfort activities. This study uses secondary data collection methods, then calculated in three models of variations in the condition of the retaining wall to obtain stability and structural analysis which can then calculate the value of bolster safety and sliding safety in buildings. Based on the calculation results obtained as follows, the capacity value of the soil behind the building of the retaining wall is qa = qu / 3 = 17.933 t/m^2 where the safety factor = 3.00 is normal qae = qu / 2 = 26,900 t/m^2 where the safety factor = 2.00 earthquake conditions. The value of stability and analysis of the structure of the retaining wall against rolling is Fg = 3.027>1.5, the shear is Fs = 1.587> 25.25 and foundation reinforcement 221.5 and the minimum stress value of qmin = 3.8006 tons/m² and the maximum stress value of qmax = 9.6454 tons/m² . The reinforcement design of the walls and the foundation of the soil retaining building to be safe against landslides is to reinforce 1925 the walls using 2225. guide